Contracts and Inequity Aversion - Florian Englmaier; Achim Wambach (Center for Economic Studies and ifo Institute (CESifo), 2002)
Using the concept of Inequity Aversion we derive in a Moral Hazard setting several results which differ from conventional contract theory. Our three key insights are: First, inequity aversion plays a crucial role in the design of optimal contracts. Second, there is a strong tendency towards linear sharing rules, giving a simple and plausible rationale for the prevalence of these schemes in the real world. Third, the Sufficient Statistics result no longer holds as optimal contracts may be too complete. Along with these key insights we derive a couple of further results.
Keywords: D63; J30; M12; Z13; 330; contract theory; linear contracts; incentives; sufficient statistics result; inequity aversion; fairness